Improving Students' Short Story Writing Skills: A Study on the Effects of Problem Based Learning with Image Media - Halawa, Noibe; Lisaria zalukhu; Merci Lestariani Lahagu; Junius Laoli (EDUPEDIA Publisher, 2023)
: One of the language components is writing, and the skill of writing short stories is a part of learning Indonesian, as well as being a literary work in the form of narrative prose with relatively short stories. Although Indonesian language subject teachers have tried to teach their students by using various learning models to improve short story writing skills, the expected learning outcomes are difficult to achieve. But it is believed that improving students' short story writing skills can be improved by teaching them with problem-based learning models assisted by media images. The purpose of this study was to reveal students' writing skills in short story texts before and after being taught with the Problem Based Learning learning model with the Assistance of Picture Media. This study used an experimental method, the respondents were a group of students who were given a pretest before being given treatment, namely learning with this learning model and after that they were given a posttest. The source of the research data was a study group of class VIII students of SMP (junior high school) N 4 Lahewa. The results of the study concluded that there was a significant increase in students' short story writing skills after being taught with the problem-based learning model assisted by media images. Before being taught with this learning model, students' short story writing skills were in the poor category, whereas after being taught with this learning model, their skills in writing were in the very good category. So it is suggested to Indonesian language subject teachers to use this learning model to improve students' ability to write short story texts